Brand Authenticity and Strategic Response to Crises: Symbolic Effects of Donation Type on Purchase Intent and Digital Engagement. Issue 3 (28th August 2021) - Pittman, Matthew; Sheehan, Kim
Abstract: Brand Authenticity is paramount in contemporary advertising and brands can communicate their authenticity by supporting social and environmental crises. Brands often donate money or products to causes, and while the value of such activities has been documented, the actual nature of the donation relative to authenticity and subsequent outcomes is unclear. How much should brands donate? What type of donation is best? What are the advantages of choosing certain crises over others? This paper explores how a brand's authenticity might be affected by its response strategy to various crises. Two experimental studies provide converging evidence that with either an acute (a weather-related crisis) or a chronic social (school funding) issue, the right type and size of donation can lead to desirable brand outcomes while assisting those in need. We argue that symbolic consumption is the mechanism through which process occurs. We find that purchase intent can be generated through donating cash or products to a crisis that fits well with brand values, whereas digital engagement is best generated through product donation in support of a crisis which does not.